Implementasi Problem-Based Learning (PBL) untuk Meningkatkan Pemahaman Peserta Didik pada Tema Aku Memiliki Kemampuan pada Kelas 7 Fase D di SMPN 1 Embaloh Hulu - Silvester Nyawai; Brigida Intan Printina; Vinsensius Kriswidiatma Tjahja Hernawa (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to find out how the implementation of Problem-Based Learning (PBL) can increase students' understanding of the theme My Abilities and Limitations in Phase D at SMPN 1 Embaloh Hulu. Apart from that, this research also aims to measure the effectiveness of PBL in increasing students' understanding of their abilities and limitations, as well as analyzing changes in students' attitudes and understanding of this theme after implementing PBL. This research is classroom action research. The samples in this research were class VII students. The instrument used is a test to measure students' conceptual understanding of the material My Abilities and Limitations. The action is carried out in two cycles, at the end of each cycle, students are given a problem understanding test on the My Capabilities and Limitations material. The results obtained show a significant increase in students' understanding after implementing PBL. In cycle 1, the average student score was 69.63 with 75% completeness, but after implementing PBL more intensively in cycle 2, the average score increased to 83.31 with 94% completeness. PBL not only improves cognitive aspects, but also helps students reflect on their abilities and limitations.